Knowledge, Attitudes, and Practices of nurses regarding blood culture collection - Juliana Silva Ruiz; Oleci Pereira Frota; Marcos Antonio Ferreira Júnior (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to investigate the knowledge, attitudes, and practices of nurses regarding blood culture collection. Methods: a cross-sectional study was conducted in five Brazilian public hospitals with 112 nurses. Data were collected using an adapted questionnaire and analyzed through descriptive and inferential statistics. Results: nurses who did not consider themselves capable of collecting blood cultures had a 72% lower chance of performing the collection at the recommended site and an 83% lower chance of using the same needle for blood inoculation into the vials. Nurses working in the emergency department had a 75% lower chance of knowing the international benchmark for blood culture contamination rates, and those with less than 5 years in the position decreased their chance of accuracy in this matter by 79%. Conclusions: there are gaps in the knowledge, attitudes, and practices of nurses regarding blood culture collection. Standardization of the technique, periodic education, supervision and guidance of the collection team, and process auditing are recommended coping strategies.